A review of the emergent ecosystem of collaborative geospatial tools for addressing environmental challenges. (September 2017) - Palomino, Jenny; Muellerklein, Oliver C.; Kelly, Maggi
Abstract: To solve current environmental challenges such as biodiversity loss, climate change, and rapid conversion of natural areas due to urbanization and agricultural expansion, researchers are increasingly leveraging large, multi-scale, multi-temporal, and multi-dimensional geospatial data. In response, a rapidly expanding array of collaborative geospatial tools is being developed to help collaborators share data, code, and results. Successful navigation of these tools requires users to understand their strengths, synergies, and weaknesses. In this paper, we identify the key components of a collaborative Spatial Data Science workflow to develop a framework for evaluating the various functional aspects of collaborative geospatial tools. Using this framework, we then score thirty-one existing collaborative geospatial tools and apply a cluster analysis to create a typology of these tools. We present this typology as a map of the emergent ecosystem and functional niches of collaborative geospatial tools. We identify three primary clusters of tools composed of eight secondary clusters across which divergence is driven by required infrastructure and user involvement. Overall, our results highlight how environmental collaborations have benefitted from the use of these tools and propose key areas of future tool development for continued support of collaborative geospatial efforts. Highlights: Frameworks for evaluating geospatial tools need to include their support for collaborative tasks In recent years, numerous multi-user geospatial tools have been developed, creating some confusion for users A quantitative and repeatable framework was developed to create a typology of collaborative geospatial tools Three primary clusters of tools are identified; divergences are driven by required infrastructure and user involvement This typology highlights benefits to environmental research from these tools as well as key areas of future tool development